Mental Disorders and their Relationship with Survival and Graft Rejection in Deceased Donor Kidney Transplant Recipients - Castañeda González, Héctor Octavio; García-Alanis, Mario; González-Sánchez, Judith; Morales-Buenrostro, Luis; Cabello-Rangel, Héctor (International Journal of Innovative Research in Medical Science, 2023)
Introduction: A significant association has been documented between the severity of depression and renal graft loss in post-transplant patients. Objective: To determine the relationship between mental disorders during the pre-transplant period and outcomes of graft rejection, graft loss, and mortality. Method: A retrospective cohort study was conducted on deceased donor kidney transplant recipients to assess whether mental disorders modify the risk of experiencing adverse outcomes during the post-transplant period. Results: Psychiatric comorbidity is associated with a longer duration of the pre-transplant evaluation protocol and time on the waiting list. Renal transplant candidates with psychiatric histories are more likely to experience renal graft loss compared to those without such histories. Recipients diagnosed with anxiety disorders during the pre-transplant protocol experience an increased risk of graft rejection during the post-transplantation period. Conclusion: Identifying and treating psychiatric disorders in renal transplant recipients could help reduce the likelihood of adverse outcomes during the post-transplant period. The study's main limitation is the lack of standardized instruments to identify psychiatric diagnoses during the pre-transplant evaluation protocol.